Association of oxidative stress with erectile dysfunction in community-dwelling men and men on dialysis. (31st December 2022) - Fujita, Naoki; Momota, Masaki; Ishida, Mizuri; Iwane, Takuro; Hatakeyama, Shingo; Yoneyama, Takahiro; Hashimoto, Yasuhiro; Yoshikawa, Kazuaki; Yamaya, Kanemitsu; Ohyama, Chikara
Abstract: Objectives: To investigate the association between oxidative stress and erectile dysfunction (ED) in community-dwelling men and men on dialysis. Methods: This cross-sectional study included 398 community-dwelling men and 42 men on dialysis. Oxidative stress was assessed using 8-hydroxy-2'-deoxyguanosine (8-OHdG). Univariable and multivariable logistic regression analyses were performed to evaluate the association between oxidative stress and ED. Results: Spearman's rank correlation test showed no significant correlation between urine 8-OHdG levels and the 5-Item International Index of Erectile Function scores in community-dwelling men (ρ = −0.005, p = 0.917) and between plasma 8-OHdG levels and the Sexual Health Inventory for Men scores in men on dialysis (ρ = 0.166, p = 0.295). In community-dwelling men, univariable and multivariable analyses revealed that urine 8-OHdG level was not significantly associated with ED (odds ratio [OR]: 1.005, 95% confidence interval [CI]: 0.884–1.144, p = 0.934; OR: 0.930, 95% CI: 0.798–1.084, p = 0.353; respectively). In men on dialysis, univariable analyses revealed that plasma 8-OHdG level was not significantly associated with severe ED (OR: 0.967, 95% CI: 0.876–1.066, p = 0.498). Conclusions: Oxidative stress was not significantly associated with ED prevalence and severity in community-dwelling men and men on dialysis.